The Effect of the #WasteDown Beauty Up Campaign Message on Instagram on Environmental Awareness on Sociolla’s Instagram Followers - Revina Larasati; Lusia Handayani; Vina Mahdalena (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Human life today is closely related to the use of plastic. Plastics are used in a variety of activities and for various purposes. Besides the convenience and perceived benefits, excessive use of plastic can also harm the environment. It is a common problem because of the excessive and continuously increasing use of plastic and the need for public awareness of their responsibility towards waste. This study aims to determine the effect of the #WasteDownBeautyUp message on Instagram on the environmental awareness of Sociolla's Instagram followers using the Nowak and Warneryd campaign models. The method used in this research is quantitative. Researchers used the survey method to distribute questionnaires to 100 respondents, namely followers of the Instagram account @sociolla, with a purposive sampling technique. The results showed that the t-count value was 3.637 > t-table 1.984 and the sig value 0.000 < 0.05, which means that Ho is rejected and Ha is accepted. The results show the effect of the #WasteDownBeautyUp campaign message on Instagram on environmental awareness among followers of Sociolla's Instagram.